Portraits of Psychiatric Reform: approximations between Brazil and Spain - Carvalho, Rafael Nicolau; Picornell-Lucas, Antonia (Argumentum, 2020)
This article presents a qualitative analysis of the deinstitutionalization experiences of Brazil and Spain to build a picture of the psychiatric reform processes within the context of a recent crisis that threatens reformist principles. The study was based on a narrative bibliographic review and documentary research. The analysis suggests that despite the historical and cultural particularities and differences in organizational arrangements for psychosocial care that permeate these countries, both have adopted deinstitutionalization as the main characteristic of their reform processes. It concludes that, currently, the contemporary reform project faces three major challenges: the dismantling of the asylum structure, strengthening the model of psychosocial care, and fighting the asylum logic.